Respuesta :
If you would like to find the equation, you can do this using the following steps:
D = b^2 - 4 * a * c
D = 12
0 = -x^2 + 8x + 2
D = 8^2 - 4 * (-1) * 2 = 64 + 8 = 72
0 = 2x^2 + 6x + 3
D = 6^2 - 4 * 2 * 3 = 36 - 24 = 12
0 = -x^2 + 4x + 1
D = 4^2 - 4 * (-1) * 1 = 16 + 4 = 20
0 = 4x^2 + 2x + 1
D = 2^2 - 4 * 4 * 1 = 4 - 16 = - 12
The correct result would be 0 = 2x^2 + 6x + 3.
D = b^2 - 4 * a * c
D = 12
0 = -x^2 + 8x + 2
D = 8^2 - 4 * (-1) * 2 = 64 + 8 = 72
0 = 2x^2 + 6x + 3
D = 6^2 - 4 * 2 * 3 = 36 - 24 = 12
0 = -x^2 + 4x + 1
D = 4^2 - 4 * (-1) * 1 = 16 + 4 = 20
0 = 4x^2 + 2x + 1
D = 2^2 - 4 * 4 * 1 = 4 - 16 = - 12
The correct result would be 0 = 2x^2 + 6x + 3.